2019
DOI: 10.1177/2325967119846915
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Reporting Recurrence After Arthroscopic Bankart Repair: A Call for a Standardized Study Design

Abstract: Background: High recurrence rates have been reported after anterior shoulder dislocations, regardless of the treatment utilized. However, the definition of recurrent instability has been inconsistent, making a comparison between studies difficult. Purpose: To report on the nature with which the rate of recurrent instability is reported after arthroscopic Bankart repair, across all levels of evidence, and to analyze factors that may affect the reported rate of recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…He introduced the frequency, etiology, direction, and severity system for describing instability. Kennedy et al 8 has described that there is a wide variety of definitions of recurrence in the literature and that the recurrence rates vary according to level of evidence, age, follow-up time, and attrition rate. Although Kennedy et al 8 have noticed that there are many different definitions used in the literature, it is still unclear how many studies did not define these definitions.…”
mentioning
confidence: 99%
“…He introduced the frequency, etiology, direction, and severity system for describing instability. Kennedy et al 8 has described that there is a wide variety of definitions of recurrence in the literature and that the recurrence rates vary according to level of evidence, age, follow-up time, and attrition rate. Although Kennedy et al 8 have noticed that there are many different definitions used in the literature, it is still unclear how many studies did not define these definitions.…”
mentioning
confidence: 99%
“…In a recent systematic review, Kennedy et al 18 reported a Bankart repair failure rate of 17.4% with a positive association to length of follow-up and the number of patients lost to follow-up. This finding is in line with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Marchant et al 22 showed that among the 3 imaging modalities, CT had a better inter-and intraobserver validity in describing bone tunnel widening after anterior cruciate ligament reconstruction. In a recent systematic review, Kennedy et al 18 reported a Bankart repair failure rate of 17.4% with a positive association to length of follow-up and the number of patients lost to follow-up. This finding is in line with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be difficult to justify early surgery in certain patient populations. In another systematic review, Kennedy et al 24 found an overall recurrence rate of 17.4% following arthroscopic Bankart repair, which suggests that postoperative results following repeated instability events are inferior compared with early stabilization. The lower non-recurrence complication rate of 1.6% reported by Hurley et al adds to the argument that young, active patients should be recommended surgical stabilization following a primary anterior shoulder dislocation.…”
mentioning
confidence: 99%
“…In this regard, we, as surgeons should follow our outcomes with a keen sense of recurrence, as either recurrent dislocation or recurrent subluxation and provide both to allow the reader important outcomes information. 24 More prospective studies with robust study design and sufficient power are needed to investigate whether the indication for surgical stabilization following the first instability event should be expanded to other patient groups. We need to standardize how recurrence of instability is reported, and we propose that recurrence include dislocation, subluxation, feeling of apprehension, and painful, unstable shoulders.…”
mentioning
confidence: 99%